INTERNATIONAL MISUNDERSTANDING IN IRRIGATION ENGINEERING - P. Ankum (Lowland Technology International, 1999)
The exchange of knowledge between irrigation engineers is quite hampered by misunderstanding. Misunderstanding can be avoid when first terminology, development concepts and fundamentals of an irrigation scheme are mutually agreed, before the technical matters are discussed. Typical topics for misunderstanding are elaborated here and include: need for large-scale development, farmer-managed or dual managed schemes, function of the tertiary unit, role of cost-recovery, need for a 'highest authority', productive and protective irrigation, design for dry-season and for wer-season irrigation, equitable and flexible supply, how is the instruction to the operator of the tertiary offtake. Most of the insfrastructural, operational and managerial matters of the irrigation scheme follow directly from choices on these topics.